Crystallization and orientation of isotactic poly(propylene) in cylindrical nanopores. Issue 21 (30th August 2014) - Reid, Dariya K.; Ehlinger, Bridget A.; Shao, Lin; Lutkenhaus, Jodie L.
ABSTRACT The crystallization of polymers in cylindrical geometries is important as interest in polymer nanowires and nanostructures grows. Here, semicrystalline isotactic poly(propylene) (iPP) is shown to crystallize in a homogeneous, low‐dimensional fashion when confined in cylindrical pores as small as 15 nm. A strong dependence on pore diameter is demonstrated. Isothermal crystallization studies suggest a reduced Avrami exponent as pore diameter decreases and as crystallization time increases. Complementary X‐ray diffraction with tilt (texture analysis) reveals one‐dimensional ordering of iPP crystals within pores of 40 nm diameter or less in which crystals preferentially orient, perpendicular to the pore wall. These findings demonstrate that the origin of this orientation is related to the impingement of crystals against the pore wall, thus "freezing out" polymer crystallizing in nonpreferred directions. These results show that curvature‐directed crystallization is one potential means to control a polymer's crystallization rate and orientation. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 1412–1419